Method for manufacturing glass member and glass member

The method enhances scratch resistance of glass members by forming a reaction layer through exposure to a water vapor-containing atmosphere and fluoride at high temperatures, addressing the limitations of conventional fluorine-containing layers and enabling cutting without surface layer removal.

JP7666010B2Active Publication Date: 2025-04-22AGC INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021025627
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-19
Publication Date
2025-04-22
Estimated Expiration
2041-02-19

AI Technical Summary

Technical Problem

Existing glass members, such as cover glass, require improved scratch resistance beyond what is provided by conventional fluorine-containing layers, which also face challenges with heat resistance and compatibility during cutting processes.

Method used

A method for manufacturing a glass member involving exposure to a water vapor-containing atmosphere at high temperatures (500° C to 900° C) while in contact with a fluoride, forming a reaction layer that enhances scratch resistance without the need for resin films.

Benefits of technology

The method achieves significantly improved scratch resistance, with the glass members exhibiting at least three times more resistance than conventional glass members, while allowing for cutting without removing the surface layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666010000005
    Figure 0007666010000005
  • Figure 0007666010000006
    Figure 0007666010000006
  • Figure 0007666010000007
    Figure 0007666010000007
Patent Text Reader

Abstract

To provide a method for producing a glass member having improved excoriation resistance in comparison with the conventional art.SOLUTION: A method for producing a glass member includes exposing glass of interest to atmosphere containing water vapor with a surface of the glass of interest kept in contact with fluoride at from 500°C to 900°C.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a glass member and a glass member. [Background technology]

[0002] Some glass members, such as cover glasses, are often required to have scratch-resistant surfaces.

[0003] The simplest method for achieving such scratch resistance is to apply a protective film, such as a resin film, to the surface of the glass member.

[0004] However, resin films have problems in terms of heat resistance. In addition, once a resin film is attached to a glass member, it may be difficult to cut the glass member. Therefore, when cutting the glass member, it is necessary to first remove the resin film from the glass member.

[0005] In Patent Document 1 filed by the present inventors, in order to address the above-mentioned problems, it is proposed to form a fluorine-containing layer on the surface of a glass member. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2019-194145 A Summary of the Invention [Problem to be solved by the invention]

[0007] In the glass member described in Patent Document 1, the fluorine-containing layer can impart a certain degree of scratch resistance to the surface. However, in recent years, there has been an increasing need for scratch resistance, and glass members are now required to have even greater scratch resistance.

[0008] The present invention has been made in view of the above background, and an object of the present invention is to provide a method for manufacturing a glass member having better scratch resistance than conventional methods. Another object of the present invention is to provide a glass member having better scratch resistance than conventional methods. [Means for solving the problem]

[0009] The present invention provides a method for producing a glass member, comprising the steps of: The method includes exposing the glass to be treated to an atmosphere containing water vapor at a temperature of 500° C. to 900° C. while the surface of the glass is in contact with a fluoride.

[0010] The present invention also provides a glass member having a surface, comprising: The reflection characteristic profile obtained by infrared reflection spectroscopy at the surface at an angle of 10° to the normal was measured at a wave number of 920 cm -1 ~980cm -1 A first peak region having a peak in the range of wavenumber 1040 cm -1 ~1120cm -1 and a second peak region in the range of, and the area of ​​the first peak region is S1 and the area of ​​the second peak region is S2, A glass member is provided in which the ratio S1 / S2 is 0.8 or greater. Effect of the Invention

[0011] The present invention can provide a method for producing a glass member having better scratch resistance than conventional methods. Also, the present invention can provide a glass member having better scratch resistance than conventional methods. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a schematic diagram showing peak separation of a reflection spectrum obtained by infrared reflection spectroscopy. [Diagram 2]1 is a cross-sectional view showing a schematic configuration example of a glass member according to an embodiment of the present invention. [Diagram 3] 1 is a photograph showing an example of the surface of a smooth surface layer taken with a scanning electron microscope (SEM). [Figure 4] 1 is a photograph showing an example of the surface of a textured surface layer taken with an atomic force microscope (AFM). [Diagram 5] FIG. 2 is a diagram showing an example of a reflection spectrum of a concave-convex surface layer obtained by infrared reflection spectroscopy. [Figure 6] 1A to 1C are diagrams illustrating a flow of a method for manufacturing a glass member according to an embodiment of the present invention. [Figure 7] 1A to 1C are diagrams illustrating a schematic diagram of a process for producing a glass member according to an embodiment of the present invention. [Figure 8] 1A to 1C are diagrams illustrating a schematic diagram of a process for producing a glass member according to an embodiment of the present invention. [Figure 9] 5A to 5C are diagrams illustrating a flow of a method for manufacturing a glass member according to another embodiment of the present invention. [Figure 10] FIG. 2 is a diagram showing an example of the reflection spectrum of Sample 1 obtained by infrared reflection spectroscopy. [Figure 11] FIG. 2 is a diagram showing an example of the reflection spectrum of sample 11 obtained by infrared reflection spectroscopy. [Figure 12] FIG. 2 is a diagram showing an example of the reflection spectrum of sample 21 obtained by infrared reflection spectroscopy. [Figure 13] FIG. 2 is a diagram showing an example of a reflection spectrum of sample 24 obtained by infrared reflection spectroscopy. [Figure 14] FIG. 2 is a graph showing the concentration profile of each element in the depth direction of the surface layer obtained in Sample 1. [Figure 15] 1 is a diagram showing the concentration profile of each element in the depth direction of the surface layer obtained in Sample 11. FIG. [Figure 16] FIG. 11 is a diagram showing a collection of micrographs of the surfaces of the samples after the scratch resistance test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.

[0014] In one embodiment of the present invention, A method for manufacturing a glass member, comprising: The method includes exposing the glass to be treated to an atmosphere containing water vapor at a temperature of 500° C. to 900° C. while the surface of the glass is in contact with a fluoride.

[0015] In one embodiment of the present invention, a glass member having a surface layer on its surface is manufactured. The surface layer is formed as a reaction layer of the glass to be treated. Therefore, in one embodiment of the present invention, unlike the case where a resin film is attached to the surface of a glass substrate, the glass member can be cut while still containing the surface layer.

[0016] Furthermore, this surface layer has better scratch resistance than a conventional fluorine-containing layer, and therefore the manufacturing method according to one embodiment of the present invention can provide a glass member having better scratch resistance than conventional glass members.

[0017] In addition, in one embodiment of the present invention, 1. A glass member having a surface, The reflection characteristic profile obtained by infrared reflection spectroscopy at the surface at an angle of 10° to the normal was measured at a wave number of 920 cm -1 ~980cm -1 A first peak region having a peak in the range of wavenumber 1040 cm -1 ~1120cm -1 and a second peak region in the range of, and the area of ​​the first peak region is S1 and the area of ​​the second peak region is S2, A glass member is provided in which the ratio S1 / S2 is 0.8 or greater.

[0018] The glass member according to an embodiment of the present invention is characterized in that the number of non-bridging oxygen atoms on the surface is relatively large, and therefore the aforementioned ratio S1 / S2 exhibits a relatively high value of 0.8 or more.

[0019] In such a glass member, the scratch resistance of the surface can be significantly improved.

[0020] For example, the glass member according to one embodiment of the present invention can achieve scratch resistance that is at least three times higher than that of the glass member described in Patent Document 1 mentioned above.

[0021] Here, the peak separation technique used in the present application will be described with reference to FIG.

[0022] As described above, in this application, the reflectance spectrum of the surface of the object is measured by infrared reflectance spectroscopy, and the measurement is performed at an angle of 10° with respect to the normal to the surface of the object.

[0023] FIG. 1 shows a schematic example of a measured reflectance spectrum.

[0024] This reflectance spectrum 10 is then separated into two peak regions 20,30.

[0025] Specifically, in the reflection spectrum 10, the wave number is 920 cm -1 ~980cm -1 The first peak is located between 1040 cm and 1050 cm. -1 ~1120cm -1 The second peak is defined between the first and second peak regions 20 and 30. Next, a curve fitting method is used to determine the first peak region 20 and the second peak region 30 so that the sum of the squares of the differences between the actual reflectance spectrum 10 and the calculated spectrum is minimized.

[0026] Such an operation can be easily carried out by using commercially available peak separation software (eg, Orijin software).

[0027] The above-mentioned S1 and S2 are the area integral values ​​of the first peak region 20 and the second peak region 30, respectively.

[0028] In the case of glass, the first peak is derived from non-bridging oxygen, and the second peak is derived from bridging oxygen. In addition, in the case of a general glass substrate, bridging oxygen is preferentially present on the surface. Therefore, in the case of a general glass substrate, unlike FIG. 1, the area of ​​the second peak region 30 tends to be larger than the area of ​​the first peak region 20 (for example, the ratio S1 / S2 is about 0.5).

[0029] In contrast, in a glass member according to an embodiment of the present invention, the non-bridging oxygen is relatively high at the surface, and therefore the area of ​​the first peak region 20 is larger than the area of ​​the second peak region 30.

[0030] In addition, in the glass member according to one embodiment of the present invention, unlike the example shown in FIG. 1, there are cases where the first peak and the second peak are clearly observed at the measured reflection spectrum 10 stage.

[0031] (Glass member according to one embodiment of the present invention) Hereinafter, a glass member according to an embodiment of the present invention will be described in more detail with reference to FIG.

[0032] FIG. 2 shows a schematic cross section of a glass member according to one embodiment of the present invention (hereinafter referred to as a "first glass member").

[0033] 2, the first glass member 100 has a first surface 102 and a second surface 104. The first glass member 100 also has a glass substrate 110 and a surface layer 130 disposed on the glass substrate 110.

[0034] The glass substrate 110 has a first surface 112 and a second surface 114, and the surface layer 130 is disposed on the first surface 112 of the glass substrate 110. However, in another embodiment of the present invention, a surface layer may be disposed on the second surface 114 as well as the first surface 112 of the glass substrate 110.

[0035] The first surface 102 of the first glass member 100 corresponds to the surface of the surface layer 130 .

[0036] Here, in the first glass member 100, the surface layer 130 is made of glass, and is characterized in that non-bridging oxygen is more prevalent than bridging oxygen.

[0037] Specifically, the surface layer 130 has a reflectance spectrum obtained by infrared reflectance spectroscopy at an angle of 10° to the normal at a wave number of 920 cm -1 ~980cm -1 A first peak region having a peak in the range of wavenumber 1040 cm -1 ~1120cm -1 and a second peak region having a peak in a range of S1 to S2, and the area (integral value) of the first peak region is S1 and the area (integral value) of the second peak region is S2, the ratio S1 / S2 is 0.8 or more.

[0038] The ratio S1 / S2 is preferably 0.9 or more, more preferably 1.0 or more, and even more preferably 1.1 or more.

[0039] Since the first glass member 100 has such a surface layer 130, it exhibits good scratch resistance.

[0040] For example, the scratch resistance of surface layer 130 of first glass member 100 may be at least three times as high as that of the glass member described in Patent Document 1, as described below.

[0041] Furthermore, in first glass member 100, scratch resistance is provided not by a resin film but by glass surface layer 130. Therefore, in first glass member 100, unlike a case in which a resin film is attached to the surface of glass substrate 110, the glass member can be cut while still containing surface layer 130.

[0042] (Regarding the surface layer 130) Other features of the surface layer 130 included in the first glass member 100 will be described in more detail below.

[0043] The configuration of the surface layer 130 having the above-mentioned characteristics can be roughly classified into two types: a first type having a smooth surface (hereinafter referred to as "smooth surface layer 130A") and a second type having an uneven surface (hereinafter referred to as "uneven surface layer 130B").

[0044] Each type of surface layer 130 will now be described.

[0045] (Smooth surface layer 130A) The smooth surface layer 130A has a smooth surface, with a surface roughness (arithmetic mean roughness Ra) in the range of, for example, 0.2 nm to 2.0 nm.

[0046] An example of the surface of the smooth surface layer 130A photographed by a scanning electron microscope (SEM) is shown in Fig. 3. It can be seen from Fig. 3 that the surface of the smooth surface layer 130A is relatively smooth.

[0047] The smooth surface layer 130A is usually characterized by a higher concentration of alkaline earth metals than the composition of the glass substrate 110. For example, in terms of atomic concentration, the total amount of alkaline earth metals contained in the bulk glass substrate 110 is expressed as C eb The sum of the concentrations of the alkaline earth metals contained in the surface layer 130 is C es In the case of the smooth surface layer 130A, the ratio C es / C eb is 1.4 or more. es / C ebis preferably 1.6 or more.

[0048] In the present application, the "concentration of the alkaline earth metal contained in the surface layer" refers to the average concentration of the alkaline earth metal obtained by measurement in the thickness direction of the surface layer.

[0049] In the present application, the total amount of alkali metals contained in the bulk glass substrate 110 is expressed as C ab The sum of the concentrations of the alkaline earth metals contained in the surface layer 130 is C as Here, the "concentration of the alkali metal contained in the surface layer" refers to the average value of the concentration of the alkali metal obtained by measurement in the thickness direction of the surface layer.

[0050] In addition, in terms of atomic concentration, the sum of the alkali metals and alkaline earth metals contained in the glass substrate 110 is represented as C2 (=C eb +C ab ), and the sum of the alkali metals and alkaline earth metals contained in the surface layer 130 is C1 (=C es +C as In this case, in the smooth surface layer 130A, the ratio C1 / C2 is 1.4 or more. The ratio C1 / C2 is preferably 1.6 or more.

[0051] Typically, the fluorine content in the smooth surface layer 130A is 10 atomic % or less. The fluorine content is preferably 5 atomic % or less, for example 3 atomic % or less, or may be substantially zero.

[0052] The thickness of the smooth surface layer 130A is not particularly limited. The thickness of the smooth surface layer 130A is, for example, in the range of 50 nm to 1000 nm. The thickness of the smooth surface layer 130A is preferably in the range of 100 nm to 500 nm.

[0053] The above-mentioned FIG. 1 diagrammatically shows an example of a typical infrared reflectance spectrum observed in the first glass member 100 having the smooth surface layer 130A.

[0054] 1, in the first glass member 100 having the smooth surface layer 130A, when the measured infrared reflection spectrum 10 is peak-separated, the first peak region 20 is larger than the second peak region 30. As described above, the area ratio S1 / S2 of both regions 20, 30 is 0.8 or more.

[0055] (Uneven surface layer 130B) Next, the uneven surface layer 130B will be described.

[0056] The uneven surface layer 130B has a surface with fine unevenness, unlike the smooth surface layer 130A. This is because at least a part of the surface of the uneven surface layer 130B has an aggregate of "nanoparticles" or the surface of the uneven surface layer 130B is at least partially composed of an aggregate of "nanoparticles."

[0057] Here, the term "nanoparticles" refers to fine particles with an average particle size of 8 nm to 15 nm.

[0058] An example of the surface of the uneven surface layer 130B photographed by an atomic force microscope (AFM) is shown in Figure 4. In Figure 4, the vertical and horizontal dimensions of the image are 100 nm x 100 nm.

[0059] 4, it can be seen that the surface of the uneven surface layer 130B is in the form of an aggregation of numerous nanoparticles, with many projections and recesses present. Each nanoparticle has a diameter of approximately 10 nm.

[0060] The textured surface layer 130B primarily contains silicon and oxygen.

[0061] In terms of atomic concentration, the total of silicon and oxygen contained in the uneven surface layer 130B is 98% or more, and preferably 99% or more. In particular, it is preferable that the uneven surface layer 130B is composed of silicon and oxygen.

[0062] In terms of atomic concentration, the silicon to oxygen ratio O / Si in the uneven surface layer 130B is 2.2 or more. Since the ratio O / Si in normal silicon dioxide is 2.0, this ratio value in the uneven surface layer 130B is characteristic.

[0063] The thickness of the uneven surface layer 130B is not particularly limited. The thickness of the uneven surface layer 130B is, for example, in the range of 50 nm to 1000 nm. The thickness of the uneven surface layer 130B is preferably in the range of 100 nm to 500 nm.

[0064] FIG. 5 shows a schematic example of a typical infrared reflectance spectrum observed in a first glass member 100 having a textured surface layer 130B.

[0065] As shown in FIG. 5, in the first glass member 100 having the uneven surface layer 130B, two peaks corresponding to the first peak region 20 and the second peak region 30 appear more clearly than in FIG. 1.

[0066] However, even in this case, the area ratio S1 / S2 is 0.8 or more.

[0067] (Method of manufacturing a glass member according to one embodiment of the present invention) Next, a method for manufacturing a glass member according to an embodiment of the present invention will be described with reference to FIG.

[0068] FIG. 6 shows a schematic flow of a method for producing a glass member according to one embodiment of the present invention (hereinafter referred to as the "first method").

[0069] As shown in FIG. 6, the first method is: (1) a step of exposing the glass to be treated to a water vapor-containing atmosphere at a high temperature while the surface of the glass to be treated is in contact with a fluoride (step S110); (2) removing fluoride (step S120); has.

[0070] In the first method, for example, a glass member having the above-mentioned smooth surface layer 130A can be produced.

[0071] Each step will be described below. Note that, as an example, the manufacturing method will be described using the above-mentioned first glass member 100. Therefore, the reference symbols used in FIG. 2 will be used to represent each part.

[0072] (Step S110) First, a glass to be processed is prepared. The glass to be processed may be a glass substrate 110.

[0073] The composition of the glass substrate 110 is not particularly limited as long as it is made of glass. The glass substrate 110 may be, for example, soda-lime glass.

[0074] There is no particular limitation on the shape of the glass substrate 110. The glass substrate 110 may be, for example, in the shape of a plate, a disk, or a block.

[0075] Next, fluoride is applied to the surface to be treated (referred to as the first surface 112) of the glass substrate 110.

[0076] The type of fluoride is not particularly limited as long as it is a solid. The fluoride may include, for example, at least one of an alkali metal fluoride and an alkaline earth fluoride.

[0077] The manner in which the fluoride is provided is not particularly limited, and the fluoride may be provided on the first surface 112 of the glass substrate 110, for example, as particles or as a layer.

[0078] The following will be described as an example where the fluoride is provided as a layer.

[0079] If the fluoride is a layer, the fluoride layer may be applied by any method to the first surface 112 of the glass substrate 110. The fluoride layer may be applied to the first surface 112 of the glass substrate 110 by a method such as, for example, evaporation, PVD, CVD, or sputtering.

[0080] Alternatively, the fluoride layer may be formed on the first surface 112 as a reaction product with glass by supplying hydrogen fluoride (HF) gas to the glass substrate 110. In this case, the concentration of the HF gas is preferably in the range of 1 vol% to 20 vol%. The treatment temperature is preferably in the range of 200°C to 650°C.

[0081] The method of forming a fluoride layer on the glass substrate 110 using HF gas is described in detail in the above-mentioned Patent Document 1.

[0082] FIG. 7 is a schematic diagram showing a state in which a fluoride layer 120 is provided on a first surface 112 of a glass substrate 110. As shown in FIG.

[0083] The glass substrate 110 is then exposed to a water vapor-containing atmosphere at an elevated temperature.

[0084] For this purpose, for example, the glass substrate 110 may be placed in a processing chamber, and the inside of the processing chamber may be heated and a gas containing water vapor may be supplied into the processing chamber.

[0085] The gas containing water vapor may be supplied in a state of being mixed with a carrier gas, such as argon and / or nitrogen.

[0086] The partial pressure of water vapor in the atmosphere is, for example, in the range of 0.5 vol% to 100 vol%. The partial pressure of water vapor is preferably in the range of 1 vol% to 20 vol%.

[0087] The processing temperature is 500°C or higher and lower than the melting temperature of the glass substrate 110. For example, the processing temperature is in the range of 500°C to 900°C. The processing temperature is preferably in the range of 600°C to 800°C.

[0088] The treatment time varies depending on the treatment temperature and the water vapor partial pressure, but may be in the range of, for example, 1 minute to 24 hours.

[0089] FIG. 8 shows a schematic of a glass substrate 110 having a fluoride layer 120 after processing in a high temperature processing chamber.

[0090] By this treatment (hereinafter referred to as “water vapor treatment”), a reaction layer 129 is formed on the first surface 112 of the glass substrate 110 directly below the fluoride layer 120.

[0091] The thickness of the reaction layer 129 is in the range of 50 nm to 1000 nm, for example.

[0092] (Process S120) The fluoride layer 120 is then removed from the first surface 112 of the glass substrate 110 to expose the reaction layer 129 .

[0093] The method for removing the fluoride layer 120 is not particularly limited. The fluoride layer 120 may be removed mechanically. For example, the fluoride layer 120 may be removed by polishing the surface of the glass substrate 110 with a tool such as a brush or an abrasive material.

[0094] This makes it possible to manufacture a glass member having surface layer 130 (reaction layer 129) as shown in Fig. 1. As described above, in the first method, smooth surface layer 130A is formed as surface layer 130.

[0095] (Method of manufacturing a glass member according to another embodiment of the present invention) Next, a method for manufacturing a glass member according to another embodiment of the present invention will be described with reference to FIG.

[0096] FIG. 9 shows a schematic flow of a method for producing a glass member according to another embodiment of the present invention (hereinafter referred to as the "second method").

[0097] As shown in FIG. 9, the second method is: (1) a step of exposing the glass to be treated to a water vapor-containing atmosphere at a high temperature while the surface of the glass to be treated is in contact with a fluoride (step S210); (2) removing fluoride (step S220); (3) treating the glass to be treated with hydrochloric acid (step S230); has.

[0098] In the second method, steps S210 to S220 are the same as steps S110 to S120 in the above-described first method, so here, step S230 will be explained.

[0099] In the second method, step S220 does not necessarily have to be performed, because fluoride can be dissolved and removed by the hydrochloric acid treatment depending on the treatment conditions in step S230.

[0100] (Step S230) After the water vapor treatment (step S210) or the fluoride removal treatment (step S220), the glass substrate 110 is treated with hydrochloric acid (hereinafter referred to as "hydrochloric acid treatment").

[0101] If fluoride remains on the surface, the fluoride can be dissolved and removed by the hydrochloric acid treatment, and the reaction layer 129 is modified by the hydrochloric acid treatment to form a modified layer.

[0102] The conditions for the hydrochloric acid treatment are not particularly limited. For example, the hydrochloric acid treatment may be performed by immersing the glass substrate 110 having the reaction layer 129 in a hydrochloric acid bath for a predetermined time.

[0103] The hydrochloric acid concentration is, for example, in the range of 1 wt % to 17.5 wt %. The hydrochloric acid treatment may be carried out at room temperature or in a heated state.

[0104] In the second method, for example, a glass member having the aforementioned uneven surface layer 130B can be produced.

[0105] The method for producing a glass member according to an embodiment of the present invention has been described above using the first and second methods as examples.

[0106] However, the above description is merely an example, and the glass member according to the embodiment of the present invention may have other processes. For example, in the first method, the fluoride layer 120 is removed by mechanical polishing. However, the fluoride layer 120 may be removed by a chemical process or a mechanical and chemical process (e.g., a chemical mechanical polishing (CMP) process).

[0107] Many other modifications are possible. EXAMPLES

[0108] Examples of the present invention will now be described below. In the following description, Examples 1 to 4 and Examples 11 to 13 are Examples, while Examples 21 to 26 are Comparative Examples.

[0109] (Example 1) The glass member was prepared in the following manner.

[0110] First, a fluoride layer was formed on a first surface of a glass substrate having a length of 50 mm, a width of 50 mm, and a thickness of 0.7 mm. Dragontrail (registered trademark; AGC Corporation) was used as the glass substrate.

[0111] The fluoride layer was formed by placing the glass substrate in a processing chamber and supplying HF gas into the processing chamber at a concentration of 10 vol% at 600° C. for 4 seconds.

[0112] The thickness of the fluoride layer was targeted to be 500 nm.

[0113] Next, the glass substrate on which the fluoride layer was formed was subjected to a water vapor treatment at 600°C.

[0114] The water vapor was supplied into the treatment chamber as water vapor-containing nitrogen gas by bubbling nitrogen gas into a water tank maintained at a predetermined temperature. The concentration of water vapor was 3.6 vol%, and the treatment time was 30 minutes.

[0115] Thereafter, the surface of the glass substrate was polished to remove the fluoride layer.

[0116] Specifically, while the glass substrate was being rotated at 220 rpm, a slurry containing water and calcium carbonate was applied to the substrate, and the surface was polished with a urethane brush for about 10 seconds.

[0117] As a result, a glass member having a surface layer with a thickness of 700 nm (hereinafter referred to as "Sample 1") was obtained.

[0118] (Example 2 to Example 4) Glass members were produced in the same manner as in Example 1. However, in Examples 2 to 4, the type of glass substrate and / or the water vapor treatment conditions were changed from those in Example 1.

[0119] Glass members (hereinafter referred to as "Sample 2" to "Sample 4", respectively) were obtained from Examples 2 to 4.

[0120] (Example 11) A glass member was produced in the same manner as in Example 1. However, in Example 11, the fluoride layer was not removed after the water vapor treatment, and instead, a hydrochloric acid treatment was carried out.

[0121] The hydrochloric acid treatment was carried out by immersing the glass substrate in a hydrochloric acid solution at room temperature. The hydrochloric acid concentration in the solution was 10 wt %, and the treatment time was 10 minutes.

[0122] As a result, a glass member (hereinafter referred to as "Sample 11") was obtained.

[0123] (Example 12 to Example 13) Glass members were produced in the same manner as in Example 11. However, in Examples 12 and 13, glass substrates different from that in Example 11 were used.

[0124] Glass members were obtained from Examples 12 and 13 (hereinafter referred to as "Sample 12" and "Sample 13", respectively).

[0125] (Example 21 to Example 23) In Examples 21 to 23, untreated glass substrates were used as they were as samples (hereinafter referred to as "Sample 21" to "Sample 23", respectively).

[0126] (Example 24) In Example 24, a glass member was produced by the same method as in Example 1. However, in this Example 24, after the fluoride layer was formed, the steps subsequent to the water vapor treatment were not carried out.

[0127] As a result, a glass member (hereinafter referred to as "Sample 24") was obtained.

[0128] (Example 25~Example 26) In Examples 25 and 26, glass members were produced by the same method as in Example 24. However, in Examples 25 and 26, a glass substrate different from that in Example 24 was used as the glass substrate.

[0129] Glass members (hereinafter referred to as "Sample 25" and "Sample 26", respectively) were obtained from Examples 25 and 26.

[0130] The preparation conditions for each sample are summarized in Table 1. In Table 1, "A" in the "Glass Substrate" column indicates a Dragontrail substrate, "B" indicates a soda lime glass substrate, and "C" indicates a Dragontrail X (registered trademark; AGC Corporation) substrate.

[0131] [Table 1] (evaluation) The following evaluations were carried out using each sample.

[0132] (Infrared reflectance spectroscopy) The infrared reflectance spectrum of each sample was measured using an infrared reflectance spectrometer (Nicolet 6700; Thermo Fisher Scientific). Infrared light was incident on the surface layer side of the sample (or on the first surface side of the glass substrate if there was no surface layer). The incident angle was 10° with respect to the normal to the surface perpendicular to the thickness direction of the sample.

[0133] From the obtained spectrum, peak separation was performed by the above-mentioned method, the first peak area and the second peak area were obtained, and the ratio S1 (area of ​​the first peak area) / S2 (area of ​​the second peak area) was calculated.

[0134] Fig. 10 shows an example of the reflectance spectrum obtained for Sample 1. Fig. 10 also shows the first and second peak regions obtained by peak separation. It can be seen that the two peak regions correspond well to the actually obtained spectrum.

[0135] FIG. 11 shows an example of the reflection spectrum obtained for Sample 11. In this case too, it can be seen that the first and second peak regions correspond well to the actually obtained spectrum. For Sample 11, two peak regions were already observed in the actually measured reflection spectrum.

[0136] It is noted that from FIGS. 10 and 11, in Sample 1 and Sample 11, the first peak region is larger than the second peak region.

[0137] 12 and 13 show examples of the reflection spectra obtained in Sample 21 and Sample 24, respectively. From these results, it can be seen that in Sample 21 and Sample 24, the second peak region is larger than the first peak region.

[0138] Table 2 below summarizes the ratios S1 / S2 obtained for each sample.

[0139] [Table 2] From Table 2, it was found that in Samples 1 to 4 and Samples 11 to 13, the ratio S1 / S2 was about 1 or more. In contrast, it was found that in Samples 21 to 26, the ratio S1 / S2 was at most about 0.6.

[0140] (Surface layer analysis) The surface layers of some samples were evaluated using an X-ray photoelectron spectroscopy (XPS) device (Quantera II; ULVAC-PHI, Inc.) The measurement angle was 45° with respect to the normal to the surface of the surface layer, and a C60 ion gun was used for sputtering.

[0141] 14 and 15 show the results of concentration analysis in the depth direction of the surface layer obtained for Sample 1 and Sample 11, respectively.

[0142] 14 and 15, the interface between the surface layer and the glass substrate is located at a depth of about 700 nm.

[0143] It can be seen from FIG. 14 that in Sample 1, the surface layer has increased concentrations of Mg and Na compared to the glass substrate.

[0144] On the other hand, it can be seen from Fig. 15 that in the case of Sample 11, the surface layer contains almost only Si and O. The sum of the Si concentration and the O concentration was about 98 at %.

[0145] From the results obtained for each sample, the ratio C es / C eb , ratio C1 / C2, and ratio O / Si were evaluated. As mentioned above, C es represents the total concentration of alkaline earth metals in the surface layer, and C ebrepresents the sum of the alkaline earth metals contained in the glass substrate, C1 represents the sum of the alkali metals and alkaline earth metals contained in the surface layer, and C2 represents the sum of the alkali metals and alkaline earth metals contained in the glass substrate.

[0146] Table 3 below shows the C values ​​obtained for each sample. es / C eb , C1 / C2, and O / Si are shown together.

[0147] [Table 3] Samples 1, 4, and 5, which were only subjected to steam treatment, all had a ratio of es / C eb The ratios C1 / C2 were all above 1.4.

[0148] In contrast, in samples 11 to 13, which were treated with hydrochloric acid, the ratio C es / C eb was at most 0.11, and the ratio C1 / C2 was at most 0.21.

[0149] Moreover, in Samples 11 to 13, the ratio O / Si was 2.2 or more.

[0150] The surface of the surface layer of Sample 1 was relatively smooth, and had the surface morphology shown in Fig. 3. On the other hand, the surface of the surface layer of Sample 11 was crater-like, and had the surface morphology shown in Fig. 4.

[0151] (Scratch resistance test) The scratch resistance of each sample was evaluated using a scratch resistance tester (TYPE: 3822; Tribogear, manufactured by Shinto Scientific Co., Ltd.).

[0152] Specifically, a Si3N4 needle (diameter 50 μm) was linearly moved (scanned) at a speed of 20 mm / min under a load of 100 g on the surface layer of each sample (or the first surface of the glass substrate if no surface layer was present) to generate scratches on the surface of the sample. The needle traveled a distance of 30 mm.

[0153] To facilitate observation, the surfaces of the samples were etched with a 1 wt % hydrofluoric acid solution after the test.

[0154] After etching, the number of arch-shaped scratches present in a 1.4 mm wide area was counted at the approximate center of the stylus's scanning track, and the scratch density (number / mm 2 ) was calculated.

[0155] The same measurement was carried out twice at different positions, and the average of the flaw density was calculated as the “average flaw density A ave " and evaluated it as such.

[0156] FIG. 16 shows a summary of the micrographs of the surface of each sample after the test. Table 4 below shows the average flaw density A obtained for each sample. ave The following is a summary.

[0157] [Table 4] From Table 4, the average scratch density A for samples 21 to 26 ave The minimum is 31 pieces / mm 2 On the other hand, in samples 1 to 4 and samples 11 to 13, the average flaw density A ave The maximum number of pieces is 15.0 / mm 2 The results are as follows, and it was found that the values ​​are small.

[0158] For example, a comparison of the results for Sample 11, which has the same glass substrate, and the untreated Sample 21 shows that Sample 11 has a higher average scratch density A than Sample 21. aveIt was found that the average scratch density A was reduced to about 1 / 45. In addition, a comparison of the results for Sample 11 and Sample 24 (which were treated with HF gas only) using the same glass substrate showed that Sample 11 had a lower average scratch density A than Sample 24. ave was found to be reduced to about 1 / 15.

[0159] Thus, it was confirmed that Samples 1 to 4 and Samples 11 to 13 had significantly improved surface scratch resistance.

[0160] Furthermore, a comparison of samples having the same glass substrate (e.g., Sample 1 and Sample 11, Sample 4 and Sample 12, Sample 5 and Sample 13) revealed that not carrying out the hydrochloric acid treatment provided better scratch resistance than did carrying out the hydrochloric acid treatment. [Explanation of symbols]

[0161] 10 Reflectance Spectrum 20 First peak area 30 Second Peak Area 100 First glass member 102 First surface of first glass member 104 Second surface of first glass member 110 Glass substrate 112 First surface of glass substrate 114 Second surface of glass substrate 120 Fluoride Layer 129 Reaction Layer 130 Surface layer 130A Smooth surface layer 130B Uneven surface layer

Claims

1. 1. A glass member having a surface, The reflection characteristic profile obtained by infrared reflection spectroscopy at the surface at an angle of 10° to the normal was measured at a wave number of 920 cm -1 ~980cm -1 A first peak region having a peak in the range of wave number 1040 cm -1 ~1120cm -1 and a second peak region in the range of 1 The area of ​​the second peak region is S 2 When ratio S 1 / S 2 is 0.8 or more.

2. the glass member has a surface layer; The glass member according to claim 1 , wherein the surface corresponds to a surface of the surface layer.

3. the surface layer has a fluorine concentration of less than 10 atomic %; In atomic concentration notation, the concentration of the alkaline earth metal in the surface layer is C es and the concentration of alkaline earth metal in the bulk of the glass member is C eb When Ratio C es / C eb The glass member according to claim 2 , wherein the refractive index is 1.4 or greater.

4. In atomic concentration notation, the sum of the alkaline earth metal concentration and the alkali metal concentration in the surface layer is C 1 The sum of the alkaline earth metal concentration and the alkali metal concentration in the bulk of the glass member is C 2 When Ratio C 1 / C 2 The glass member according to claim 3 , wherein the refractive index is 1.4 or greater.

5. the surface layer comprises silicon and oxygen; In terms of atomic concentration, the sum of the silicon and the oxygen is 98% or more; 3. The glass member according to claim 2, wherein, in atomic concentration notation, a ratio of silicon to oxygen, O / Si, is 2.2 or more.

6. The glass member according to claim 5 , wherein at least a portion of the surface of the surface layer is composed of an aggregate of nanoparticles.

Citation Information

Patent Citations

  • Aluminum phosphate compounds, compositions, materials, and related composites

    JP2005535554A

  • Glass substrate

    JP2019194145A

  • Method for producing surface-treated glass substrate

    WO2012141310A1

  • Glass plate and process for manufacturing glass plate

    WO2014167842A1